KONTRADIKSI HADIS LARANGAN SALAT SESUDAH SUBUH DAN ASHAR (KAJIAN MUKHTALIF AL-ḤADĪṠ) - Ginting, Ernawati Beru (Institut Agama Islam Ngawi, 2024)
One of the sunnah prayers recommended by the Prophet Muhammad. is the sunnah prayer of careib. The sunnah careib prayer is a prayer that is performed before or after the fardu prayer, or that accompanies the fardu prayer. Rasulullah saw. recommends his people to perform sunnah prayers as a complementary form of fardu prayers, with the aim of covering deficiencies that may occur when performing fardu prayers, because not everyone can perform fardu prayers perfectly. However, there are two times where no sunnah prayers are recommended, namely after the morning prayer and after the afternoon prayer. However, there is a hadith narrated that one of the Prophet's companions, namely Qais bin 'Amr, performed two rak'ahs of sunnah prayer after dawn. Based on these differences, it appears that there is a potential conflict between these two pieces of information. Therefore, the aim of this research is to find common ground and compromise these two seemingly contradictory hadiths. Problem Formulation: What is the form of compromise in the hadith that discusses the prohibition of performing prayers after dawn. Research Objective: This study aims to examine the compomise contained in the hadith regarding the prohibition of performing prayers after dawn. It can be concluded that the two arguments that appear contradictory at first glance can actually be harmonized . Both have the same meaning in the application of the law, namely the prohibition of performing any sunnah prayer after dawn. However, the hadith narrated by the companion Qais, which allows performing the sunnah prayer of dawn after dawn, is considered an exception to the prohibition. Thus, the It is forbidden to perform sunnah prayers after dawn other than the two sunnah rakaat of dawn.Keywords: Contraction of Hadith, Prohibition of Prayer